2022
DOI: 10.1021/acs.analchem.2c00877
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Chemiluminescence-Based POCT for Portable and Visual Pathogenic Detection and In Situ Inactivation

Abstract: Bacterial infections seriously threaten human health and also bring huge financial burden. It is critical to construct multifunctional platforms for effectively inactivating bacteria right after point-of-care testing (POCT). Chemiluminescence (CL) bioassays are considered as powerful candidates for POCT as they are free from using an excitation light source, while the flash-type emission limits their further application. Herein, a CL system with long, persistent, and intensive intensity was constructed based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…20 Our group proposed cation exchange-based CL amplification (CXCLAmp) for miRNA detection. 21 On the other hand, the visualization of CL makes it possible to develop a portable biosensor, 22,23 which is in great demand for disease diagnosis and personal health monitoring.…”
mentioning
confidence: 99%
“…20 Our group proposed cation exchange-based CL amplification (CXCLAmp) for miRNA detection. 21 On the other hand, the visualization of CL makes it possible to develop a portable biosensor, 22,23 which is in great demand for disease diagnosis and personal health monitoring.…”
mentioning
confidence: 99%
“…More interestingly, we found that CL production at this pH could last for at least 1 min (Figure c). In contrast, the no-TPY MOF, Fe/Co-MIL-88­(NH 2 ), only produced a burst of CL that decades rapidly within 20 s. The high stability of the TPY MOF, as well as the limited diffusion of the catalytic center and confined reactants within the porous MOF structures , could both contribute to the strong and long-lasting luminescence emission, which is favorable for accurate and sensitive CL analysis. , The optimal luminol concentration in the CL generation reaction was determined to be 0.032 mM (Figure S8b).…”
Section: Resultsmentioning
confidence: 99%
“…Materials with high photothermal conversion efficiency usually have complex microstructure and high light absorption capacity. [42] Taking advantage of the good photothermal properties of the nanomaterials, Chen et al [43] designed 4-mercaptophenylboronic acid (MPBA)-functionalized CuSe nanoprobes (CuSeNPs@MPBA) based on chemiluminescence (CL) for the construction of a multifunctional platform for the effective inactivation of bacteria. The nanozyme have peroxidase-like activity to catalyze the conversion of flash CL to luminescent CL, improving the stability and accuracy of the assay, as well as excellent and stable photothermal performance, with outstanding photothermal conversion efficiency (37%) that can significantly increase the temperature under NIR irradiation to cause inactivation of Escherichia coli (99.2%) and Staphylococcus aureus (99.8%).…”
Section: Photothermal Combination Therapymentioning
confidence: 99%